The Use of Problem-Based Learning to Improve Higher Order Thinking Skills of fifth-Grade Students - Handayani, Monika; Anam, Rif'at Shafwatul (Universitas Pendidikan Ganesha, 2024)
Education is expected to produce graduates who can compete and have 21st-century skills. The low ranking of Indonesian students from the results of PISA and TIMMS proves that learning is still not optimal for developing Higher-Order Thinking Skills (HOTS). This study aims to determine the influence of the Problem-Based Learning (PBL) model on HOTS in science learning for grade V elementary school students. This study uses a pretest-posttest design and is a type of quasi-experimental research. The research subjects were grade V students. Cognitive problems function to measure students' (cognitive) knowledge starting from C4 (analysing), C5 (evaluating), and C6 (creating). Meanwhile, observation sheets are used to see the process of critical thinking, creative thinking, reasoning, and decision-making skills in learning activities. The data analysis technique uses descriptive analysis techniques and t-test inferential statistical analysis techniques. The findings from the test results showed that there was a significant difference between the HOTS learning outcomes given in HOTS using PBL and students who did not use PBL. In line with the test results, the findings of the observation results also show that the HOTS ability in students who use PBL is higher than the HOTS ability in students who do not use PBL. This study provides strong empirical evidence that the PBL model can be an effective strategy to improve students' HOTS abilities.